Posted by **Anonymous** on Tuesday, March 5, 2013 at 1:29pm.

if f(x) =x+3/7 and g(x) =4+5x find (gof) (x)

- College math -
**Dr. Jane**, Tuesday, March 5, 2013 at 1:34pm
Replace the x is the f(x) by the values for g(x)

for the x is the f(x) you would write 4 + 5x + 3/7

I don't know if the problem is

(x+3) all divided by 7

or if it is x added to 3/7

- College math -
**Steve**, Tuesday, March 5, 2013 at 2:43pm
(g◦f)(x) = g(f(x))

g(x) = 4+5x, so

g(f) = 4 + 5f

= 4+5(x+3/7)

and we are back to Dr. Jane's question

- College math -
**Anonymous**, Tuesday, March 5, 2013 at 3:27pm
Yes it is (x+3) all divided by 7

## Answer this Question

## Related Questions

- college algebra - 1. answer the following for the given quadratic function f(x)=...
- college algebra - Given f(x) = sqrt of x+4 and g(x) = 1/x find (gof)(x).
- chemistry - Suppose the ΔGof, ΔHof, and ΔSo are available and ...
- math - Find (gof)(-2) f(x)=Squareroot of 4-x; g(x)=1-3x^2
- math - Find a. fog b. gof c. fof d. gog f(x)=4-x g(x)=3x-5
- math - (x) =pi/2-x g(x)= 5sinx/8+cos x find (gof)(pi/2) and (fof)(pi/2)
- math - If f(x)=x and g(x)=x+1 find the function and its domain: 1. gof 2. fof
- Math - Find (fog)(2) f(x)=Squareroot 4-x; g(x)=1-3x^2 Find (gof)(-2) for the ...
- math - Find a. fog b. gof c. fof d. gog for each function f(x)=4-x g(x)=3x-5
- Math - Find (fog)(2) and (gof)(-2) f(x)=Square root of 4-x; g(x)=1-3x^2 Show ...